Novel thiazolidinedione derivatives as corrosion inhibitors for mild steel and zinc in 1 M HCI - Dube-Johnstone, Nhlalo M. (My University, 2024)
Corrosion inhibition studies on mild steel (MS) and zinc in 1 M HCl were carried out at four temperatures (303.15 K, 313.15 K, 323.15 K, and 333.15 K) using eight novel thiazolidinedione derivatives (TZDs) codenamed: A1, A2, A3 (alaninates), B1, B2 (butanoates), G1, G2, and G3 (glycinates). After synthesis, the TZDs were characterized using nuclear magnetic resonance (NMR) spectroscopy. Specifically, two NMR techniques were employed: proton NMR (1H NMR) at 400MHz and carbon 13 NMR (13C NMR) at 100MHz. After characterization, five experimental techniques were employed to investigate the corrosion inhibition potential of the TZDs: weight loss (WL) analysis, potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS) and Fourier transform infrared spectroscopy (FTIR). The adsorption of the TZDs onto both metals was found to be best modelled by the Langmuir adsorption isotherm. Thermodynamic data showed that all TZDs adsorbed spontaneously onto both metal surfaces, transitioning from mixed type adsorption to chemisorption with an increase in temperature. However, WL analysis percentage inhibition (%IEWL) and activation energy (Ea) data showed that all TZDs adsorbed onto zinc via chemisorption. Data obtained from PDP analysis showed that the TZDs inhibit corrosion on MS at both anodic and cathodic sites, with a prevalence of cathodic action. However, on zinc, all TZDs inhibit corrosion exclusively at anodic sites. Data from EIS analysis showed that the adsorption of the TZDs onto both metals is a charge transfer driven process. The significantly depressed semi-circles obtained from zinc EIS data shows that capacitance plays much less of a role relative to MS, explaining the much lower phase shift (n) values obtained. Spectra obtained from FTIR analysis show that carbonyl, amine, nitro, aliphatic and aromatic functional groups all take part in the formation of an adsorption film on both metal surfaces.
Ph.D. (Chemistry)
Department of Chemistry
Keywords: UCTD